RENEWABLE ENERGY INVESTMENTS IN THE GULF COOPERATION COUNCIL COUNTRIES AND THE CHALLENGES THEY FACE - Dr. Mohammed Khairy Tawfiq Hamed Al Sheikh Abdullah (American Journals, 2023)
This study aims to demonstrate renewable energy investments in the countries of the Cooperation Council for the Arab States of the Gulf and the challenges they face. Nuclear stations such as the Emirati Barakah nuclear plant and the nuclear plant that will be built by King Abdullah City for Atomic and Renewable Energy, which aims for the peaceful use of nuclear energy, which is considered one of the largest renewable energy projects in the region as a whole. Full on power generation by traditional methods of oil and gas.
Keywords: renewable energy, Gulf Cooperation Council, Arab Gulf countries, challenges.